2020
DOI: 10.1002/ps.6049
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐TMV activity and mode of action of three alkaloids isolated from Chelidonium majus

Abstract: BACKGROUND: Plant viral diseases are difficult to control and have caused serious damage to the agricultural industry. Recently, botanical biopesticides characterized by environment friendly, safe to non-target organism and not as susceptible to produce drug resistance, have exhibited great potential to be developed as antiviral agents. To screen the natural products with antiviral effect, three alkaloids possessed anti-tobacco mosaic virus (TMV) activity were isolated from Chelidonium majus and the modes of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 44 publications
(90 reference statements)
0
16
0
Order By: Relevance
“…It has also been reported that chelerythrine has significant effects against plant viral diseases. In a recent study, anti-Tobacco Mosaic Virus (TMV) effects and mode of action of chelerythrine and some other alkaloids having antiviral activity such as chelidonine and sanguinarine were evaluated by Wenhui Guo et al The results showed that chelerythrine exhibits the best effects against TMV (at 0.5 mg mL −1 concentration) compared to other tested alkaloids [ 51 ].…”
Section: Anti-viral Activity Of Chelerythrinementioning
confidence: 99%
“…It has also been reported that chelerythrine has significant effects against plant viral diseases. In a recent study, anti-Tobacco Mosaic Virus (TMV) effects and mode of action of chelerythrine and some other alkaloids having antiviral activity such as chelidonine and sanguinarine were evaluated by Wenhui Guo et al The results showed that chelerythrine exhibits the best effects against TMV (at 0.5 mg mL −1 concentration) compared to other tested alkaloids [ 51 ].…”
Section: Anti-viral Activity Of Chelerythrinementioning
confidence: 99%
“…Flavonoid glycosides 2 , 5 and 6 were sprayed onto the lower three leaves of N. glutinosa at 500, 250, 125, 62.5, and 31.25 μg ml −1 , respectively, and the upper three leaves were inoculated with TMV (10 μg ml −1 ) after 24 h. Ningnanmycin and 1% DMSO were used as positive and negative controls, respectively 2 . Each treatment or control contained ten tobacco plants.…”
Section: Methodsmentioning
confidence: 99%
“…2.8 Determination of systemic resistance against TMV induced by flavonoid glycosides 2.8.1 Systemic resistance induced by 2, 5 and 6 in N. glutinosa Flavonoid glycosides 2, 5 and 6 were sprayed onto the lower three leaves of N. glutinosa at 500, 250, 125, 62.5, and 31.25 μg ml −1 , respectively, and the upper three leaves were inoculated with TMV (10 μg ml −1 ) after 24 h. Ningnanmycin and 1% DMSO were used as positive and negative controls, respectively. 2 Each treatment or control contained ten tobacco plants. The results were recorded and calculated after 4-5 days using the method described in Section 2.6.…”
Section: Protective Assaymentioning
confidence: 99%
See 2 more Smart Citations